2021
DOI: 10.1186/s13054-021-03577-7
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of depression in sepsis survivors: an observational cohort study

Abstract: Background Advances in critical care medicine have led to a growing number of critical illness survivors. A considerable part of them suffers from long-term sequelae, also known as post-intensive care syndrome. Among these, depressive symptoms are frequently observed. Depressive symptom trajectories and associated factors of critical illness survivors have rarely been investigated. Study objective was to explore and compare different trajectories of depressive symptoms in sepsis survivors over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Weakness and neuropsychiatric complications, including cognitive impairment, depression, and anxiety have been frequently described in intensive care survivors, and may persist for five or more years [ 21 23 ]. It is still debated whether long-time persistence of symptoms in patients hospitalized for COVID-19 is pathogenically similar to that observed in ICU patients admitted for other diseases or is specifically related to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Weakness and neuropsychiatric complications, including cognitive impairment, depression, and anxiety have been frequently described in intensive care survivors, and may persist for five or more years [ 21 23 ]. It is still debated whether long-time persistence of symptoms in patients hospitalized for COVID-19 is pathogenically similar to that observed in ICU patients admitted for other diseases or is specifically related to SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…We can hypothesize by analogy with studies carried out on sepsis and ARDS that this observation results from the combination of muscle loss, cognitive impairment, and psychologic issues (21, 24–27). In a recent study, Boede et al (28) showed an association between depression symptoms, chronic pain, and posttraumatic stress in the year following ICU discharge in sepsis survivors (29). This could suggest that a long-term reduction of depression symptoms compared with the general population may be linked to a resolution of chronic pain and greater acceptance of disability after several years.…”
Section: Discussionmentioning
confidence: 99%
“…Two reviewers independently extracted data on participant and study characteristics according to the guideline for data extraction for systematic reviews and meta-analysis (26), such as first author, publication years, journal, study setting (hospitalacquired or ICU-acquired), sample size, study period, sepsis type, sepsis diagnostic criteria, mean or median age, patients source, sepsis cases, comorbid conditions, number of deaths, risk factors of mortality, duration of ICU or hospital stay, type of infection, infection site and microorganisms. was then classified based on these scores as low (0-5), moderate (6)(7)(8) or high (8)(9)(10), respectively.…”
Section: Data Extractionmentioning
confidence: 99%
“…Sepsis is a major global public health concern characterized by high morbidity, high mortality, and heavy economic burden ( 4 ). Sepsis survivors often have long-term physical ( 5 ), psychological ( 6 ), and cognitive impairments ( 7 ) with significant health care and social implications. Thus, improving the prevention, recognition, and treatment of sepsis was declared as a global health priority by the World Health Organization (WHO) in 2017 ( 8 ).…”
Section: Introductionmentioning
confidence: 99%